Sequential exposure to fibroblast growth factors (FGF) 2, 9 and 18 enhances hMSC chondrogenic differentiation. Issue 3 (March 2015) - Correa, D.; Somoza, R.A.; Lin, P.; Greenberg, S.; Rom, E.; Duesler, L.; Welter, J.F.; Yayon, A.; Caplan, A.I.
Summary: Objective: To test the effects of sequential exposure to FGF2, 9 and 18 on human Mesenchymal Stem Cells (hMSC) differentiation during in vitro chondrogenesis. Design: Control and FGF2-expanded hMSC were cultured in aggregates in the presence of rhFGF9, rhFGF18 or rhFGFR3-specific signaling FGF variants, starting at different times during the chondroinductive program. Quantitative real time polymerase chain reaction (qRT-PCR) and immunocytochemistry were performed at different stages. The aggregate cultures were switched to a hypertrophy-inducing medium along with rhFGFs and neutralizing antibodies against FGFR1 and FGFR3. Histological/immunohistochemical/biochemical analyses were performed. Results: FGF2-exposed hMSC during expansion up-regulated Sox9 suggesting an early activation of the chondrogenic machinery. FGF2, FGF9 and 18 modulated the expression profile of FGFR1 and FGFR3 in hMSC during expansion and chondrogenesis. In combination with transforming growth factor-beta (TGF-β), FGF9 and FGF18 inhibited chondrogenesis when added at the beginning of the program (≤d7), while exhibiting an anabolic effect when added later (≥d14), an effect mediated by FGFR3. Finally, FGFR3 signaling induced by either FGF9 or FGF18 delayed the appearance of spontaneous and induced hypertrophy-related changes. Conclusions: The stage of hMSC-dependent chondrogenesis at which the growth factors are added impacts the progression of the differentiation program: increased cell proliferation and priming (FGF2); stimulated early chondrogenic differentiation (TGF-β, FGF9/FGF18) by shifting the chondrogenic program earlier; augmented extracellular matrix (ECM) production (FGF9/FGF18); and delayed terminal hypertrophy (FGF9/FGF18). Collectively, these factors could be used to optimize pre-implantation conditions of hMSC when used to engineer cartilage grafts.